ANALISIS DATA SEKUNDER DALAM PEMETAAN POTENSI EKONOMI BERBASIS KELURAHAN ATAU DESA DI KABUPATEN BURU - Muhammad Rusdi (SOCIETAS, 2014)
Rural areas are often not able to be developed systematically, because one of the problems is the lack of any village mapped potential for investment purposes and goals of development at the village level.This study aimed to identify a wide range of potential areas that can be economically assumed the leading sectors in the framework of regional economic structure to create a more well-established in the future. Usage patterns and use of the area of policy formulation based on the local character into the basic character of this study, by trying to make the taxonomy per local village / village at three loci, namely the village of Stone Boy, village and village Hatawano Jikumerasa.The results showed that the characteristics of the economic potential of the three villages surveyed are generally based on agriculture and plantations and coastal economy with a tendency to use a productive workforce in the manage existing economic sectors. Economic advantage at the village level with the picture of the potential of each village showed interest directly to local governments to improve the investment and reinvestment patterns are consistent with the spirit that developed in each village.Â